Ritmos de atividade diária de vôo de abelhas da subtribo Meliponina em colônia de criação no Povoado de Pedra Branca, Santa Teresinha (BA) - Gouw, Monique Sian (2011)
The stingless bees (Meliponina) are eusocial bees, living mainly in tropical and subtropical regions and often building their nests in pre-existing cavities. The worker classes of these bees normally have internal and external activities to the nest. The external activities are related to the collection of pollen and nectar, the collection of nest-building material (resin or clay) and the exit with garbage from the colony. This study aimed the investigatation and comparison of the daily outside activities of thre classes of stingless bees, namely the Melipona scutellaris, Melipona quadrifasciata and Frieseomelitta doederleini and to evaluate the presence of the daily rhythmic patterns in different months of the year, as well as the influence of environmental and meteorological factors in these activities. The largest number of activities of the species M. scutellaris and F. doederleini was observed from January to March, both considered respectively as strong and medium sized colonies. M. quadrifasciata showed a greater activity in July and August and was considered a weak sized colony. The initial activities of Melipona spp. a larger bee, generally occurred at sunrise and earlier than F. doederleini, a smaller bee. Melipona spp. showed preferential times (acrophase) of entrances, exits, entrances with pollen and resin during the mornings. F. doederlein differently, prefered usually the late mornings or early afternoons, during the different months that occurred at higher temperature values than those for Melipona spp. During the month of March, the wettest month, almost all acrophase activities for Melipona spp occurred later. The daily repetition of the first and last activities in the colony and the presence of significant acrophase for the activities of the bees in different months of the year, suggest that the presence of a daily rhythm of activity is probably influenced by the light / dark cycle, by rain and temperature. The final results of the role of environmental and meteorological factors in the external activities rhythms of the species of Meliponina studied, can only be obtained in a controlled laboratory situation.